On Chimeras - Rollin, Bernard E. (Zygon, 2007)
Abstract. This essay is a critical response to Neville Cobbe's article “Cross-Species Chimeras: Exploring a Possible Christian Perspective.” New technologies, particularly biotechnologies, raise major concerns in society. In the absence of good ethical thinking on these issues, bad ethical thinking becomes regnant. Two common types of bad ethical thinking are (1) confusing whatever disturbs people with genuine ethical issues and (2) confusing religious issues with ethical ones. Cobbe's article commits the former type of error with regard to the possibility of a mouse created with human brain neurons. I analyze and discuss that error and also raise questions about Cobbe's attempt to analyze the creation of chimeras from a Christian perspective.